2007
DOI: 10.2343/geochemj.41.65
|View full text |Cite
|
Sign up to set email alerts
|

Isotope geochemistry of the Huize Zn-Pb ore field, Yunnan Province, Southwestern China: Implication for the sources of ore fluid and metals

Abstract: The Huize ore field, which is the most famous high-grade Zn-Pb ore field in China, comprises the Kuangshanchang and Qilinchang deposits. The Zn and Pb reserves of these two deposits are more than 5 Mt with ore grades ranging from 25% to 35% in weight. Lead, sulfur, carbon, oxygen, hydrogen and strontium isotope geochemistry is reported to help understand the sources of the ore fluid and metals. Sr values may be due to the reaction between the ore fluid and the shale, clastic rocks and mudstone underlying the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…C-O-S and Pb isotopes have been widely used in previous studies for these Pb-Zn deposits in the SYG province (e.g., Zhou et al, 2001;Huang et al, 2003;Han et al, 2007;Li et al, 2007a;Zhou et al, 2013aZhou et al, , 2014aZhou et al, , 2015, whereas the studies of REE are limited Zhou et al, 2011). Therefore, the Banbanqiao Zn-Pb deposit is used as case study in this paper, by analyzing REE contents of sulfide and calcite separates, and country shale and dolostone whole-rock samples, together with new C-O isotopic data and additional S-Pb isotopic data, the authors discuss the origin of the oreforming elements, and propose a model that can account for the formation of Zn-Pb sulfide ores and provide new information for understanding the cause of a huge amount of base metals enriched in the SYG province.…”
Section: Introductionmentioning
confidence: 98%
“…C-O-S and Pb isotopes have been widely used in previous studies for these Pb-Zn deposits in the SYG province (e.g., Zhou et al, 2001;Huang et al, 2003;Han et al, 2007;Li et al, 2007a;Zhou et al, 2013aZhou et al, , 2014aZhou et al, , 2015, whereas the studies of REE are limited Zhou et al, 2011). Therefore, the Banbanqiao Zn-Pb deposit is used as case study in this paper, by analyzing REE contents of sulfide and calcite separates, and country shale and dolostone whole-rock samples, together with new C-O isotopic data and additional S-Pb isotopic data, the authors discuss the origin of the oreforming elements, and propose a model that can account for the formation of Zn-Pb sulfide ores and provide new information for understanding the cause of a huge amount of base metals enriched in the SYG province.…”
Section: Introductionmentioning
confidence: 98%
“…Rare earth element (REE) geochemistry studies can also provide information regarding the sources of ore‐forming materials (Zhao and Jiang, ). Likewise, sulphur and strontium isotopes can be used to trace the sources of S, Ca, Sr, and Ba in metallogenic systems effectively (Ruiz and Kesler, ; Barbieri and Bellanca, ; Hoefs, ; Jiang et al , ; Chen et al , , ; Zhu et al , ; Li et al , ; Wang et al , ; ). Nevertheless, the use of only single‐isotope data may yield incomplete conclusions, and it may even result in contradictory conclusions (Dejonghe et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al [1] studied the geochemical characteristics of gold orebodies hosted by different ore-bearing rocks in the Nibao gold deposit and found that all the orebodies possess a similar ore-forming source which had been mixed significantly by mantle-derived materials. It had been previously reported that the precipitation of quartz in a hydrothermal deposit has little influence on the Sr isotopic composition of the entire hydrothermal system, and thus, the 87 Sr/ 86 Sr ratio of fluid inclusions in quartz can reflect the properties of the ore-forming fluids [25,45]. Since quartz is closely associated with Carlin-type gold mineralization, variations of the Sr isotopic composition can provide indications for the ore-forming fluids and materials.…”
Section: Ore-forming Fluidsmentioning
confidence: 99%